Turnover Intention Analysis Reviewed from Happiness, Well-Being, and Work-Life Balance with Organizational Commitment as an Intervening Variable for Generation Y (Millennial) Employees at XYZ Company - Suprianto, Agus; Prasadjaningsih, Oetami (Formosa Journal of Multidisciplinary Research, 2024)
This study examines the impact of organizational commitment as an intervening variable on turnover intention in relation to happiness, well-being, and work-life balance for employees. Generation Y (millennial) at Company XYZ. The data collection technique is through distributing questionnaires using the Saturated Sampling method. Data analysis uses the Structural Equation Modeling (SEM) method based on the Smart Partial Least Square (SmartPLS) application. The research results show that the variables Happiness, Well-Being, Work Life Balance, and Organizational Commitment. Shows a negative and significant influence on the Turnover Intention of Generation Y Employees at XYZ Company.